Fluorescence-Guided Surgery (FGS) during a Laparoscopic Redo Nissen Fundoplication: The First Case in Children - Irene Paraboschi; Laura Privitera; Stavros Loukogeorgakis; Stefano Giuliani (MDPI AG, 2022)
We present the first case of fluorescence-guided surgery (FGS) using indocyanine green (ICG) in a pediatric redo-Nissen fundoplication. The patient is a 17-year-old male with recurrent gastroesophageal symptoms who underwent primary antireflux surgery at 10 months of age. During the redo fundoplication, ICG was intravenously administered to help the visualization during the adhesiolysis between liver, stomach and right crus of the diaphragm and to spare small oesophageal vessels and the left gastric artery. In this case, FGS made the surgery easier than usual and likely reduced the risk of intra-operative complications. Therefore, we believe that this new technology should be regularly used in these types of complex intra-abdominal redo operations.